Teeter-totter effect: a new mechanism to understand shoe-related improvements in long-distance running - Nigg, B. M.; Cigoja, S.; Nigg, D. (British Journal of Sports Medicine, 2021)
The effect of shoe mid-sole construction on running performance was discussed with reference to the Nike Vaporfly 4%.1 Drs Burns and Tam described the mid-sole thickness as the major running shoe characteristic that contributes to changes in performance. Here, we highlight the role of the curved carbon fibre plate embedded in the mid-sole, and introduce a new effect on running mechanics, the `teeter-totter effect`.